Визначення верхнього критичного числа Рейнольдса - Сковрінок, Мар'яна (Видавництво Національного університету «Львівська політехніка», 2009)
Experimentally the overhead Reynolds’ critical number, even 4754, and by extrapolation of dependence Re on a diameter, even 5397, is got.
Keywords: Reynolds’ number; aminar mode of motion of liquid; вода; труба